Chapter Economic and Social Aspects of the Trade of Luxury Goods between Africa and Europe: Ostrich Feather - Rizzolli, Helmut (Atti delle «Settimane di Studi» e altri Convegni, 2019)
In Europe, in the Middle Ages, ostrich feathers were used for the decoration of military headgear, as a representation of the high lineage of the possessor and his military virtues. They were imported from the coasts of West Africa, from Egypt and Syria into Italian and Spanish ports and from there exported to England and continental Europe. Venice, at the end of the fourteenth century, began to color feathers and soon the new fashion was spread throughout Europe. During the fifteenth century, even women began to use ostrich feathers on their hats or in their fans. When European ships reached America, Central Africa and the islands of the Indian Ocean, a huge amount of exotic bird feathers became available and ostrich feather fad spread through the population.